Integration of transcriptome and phytohormone analyses reveals antagonistic interactions between jasmonate and auxin signaling pathways in rice (Oryza sativa L.) - Wu, Xiaoying; Cao, Yuting; Chen, Yeye; Xiong, Wei; Cao, Gaorong; Zeng, Yan; Zhang, Liqin; Zeng, Rensen; Chen, Dongmei (Frontiers in Plant Science, 2025)
Interactions between different hormones plays a central role in plant trade-off between growth and defense. Auxin is a pivotal growth hormone and jasmonates (JA) are key hormones for plant responses to environmental stressors. In this study we examined the interactions between auxin and JA in rice (Oryza sativa L.) by integration of transcriptome and phytohormone analyses. Exogenous application of methyl jasmonate (MeJA) to rice leaves led to markedly increased accumulation of jasmonic acid (JA), MeJA, and dihydrojasmonic acid (DJA) in both leaves and roots, as well as N-jasmonic acid isoleucine (JA-Ile) in the leaves. Importantly, MeJA application significantly influenced auxin biosynthesis and orchestrated large-scale changes in transcriptional regulation of L-tryptophan (Trp) biosynthesis, as well as indole-3-acetic acid (IAA) biosynthesis, catabolism, signaling transduction, and transport in rice leaves and roots, leading to notably decreased IAA in the leaves and roots, but increased levels of indole-3-carboxylic acid (ICA) and indole-3-carboxaldehyde (ICAld) in the leaves. Our findings suggest that JA signaling suppresses auxin signaling by reducing Trp flux into the indole-3-pyruvic acid (IPA) pathway, while enhancing Trp flux into the tryptamine (TAM) pathway, thereby fine-tuning rice growth upon JA burst.